(untitled) (Patrimônio e Memória, 2025)
The Garden of the Memory of Slavery was established in 2007 as a community space symbolising the harrowing period of slavery on Africa’s East Coast and, in particular, the victims of the slave trade that ravaged Mozambique for centuries. Its existence within the city’s heritage context seeks to preserve the history and memory of the people, keeping African and Mozambican traditions alive, as various cultural events take place here. Thus, the aim was to understand the various ways in which the space is used by the island’s community and by visitors, as well as to understand their diverse forms of interpretation and appropriation of the space, considering the importance of safeguarding the heritage identity of the Island of Mozambique, giving a voice to the inhabitants of this place. Based on the literature review and documentary study, it was concluded that the appropriate methodological approach should be qualitative in nature, utilising semi-structured interviews and participant observation. The study concluded that there is some understanding of the monument’s significance and the reasons behind its construction, with particular emphasis placed on the recognition of the importance of its preservation; this partly highlights the need to intensify heritage education initiatives, with a view to fostering a sense of ownership and belonging.